Stress phase angle depicts differences in coronary artery hemodynamics due to changes in flow and geometry after percutaneous coronary intervention - Torii,R; Wood,NB; Hadjiloizou,N; Dowsey,AW; Wright,AR; Hughes,AD; Davies,J; Francis,DP; Mayet,J; Yang,GZ; Thom,SAM; Xu,XY (American Journal of Physiology - Heart and Circulatory Physiology, 2009)
Torii R, Wood NB, Hadjiloizou N, Dowsey AW, Wright AR, Hughes AD, Davies J, Francis DP, Mayet J, Yang G, Thom SA, Xu XY. Stress phase angle depicts differences in coronary artery hemodynamics due to changes in flow and geometry after percutaneous coronary intervention. Am J Physiol Heart Circ Physiol 296: H765-H776, 2009. First published January 16, 2009; doi:10.1152/ajpheart.01166.2007.-The effects of changes in flow velocity waveform and arterial geometry before and after percutaneous coronary intervention (PCI) in the right coronary artery (RCA) were investigated using computational fluid dynamics. An RCA from a patient with a stenosis was reconstructed based on multislice computerized tomography images. A nonstenosed model, simulating the same RCA after PCI, was also constructed. The blood flows in the RCA models were simulated using pulsatile flow waveforms acquired with an intravascular ultrasound-Doppler probe in the RCA of a patient undergoing PCI. It was found that differences in the waveforms before and after PCI did not affect the time-averaged wall shear stress and oscillatory shear index, but the phase angle between pressure and wall shear stress on the endothelium, stress phase angle (SPA), differed markedly. The median SPA was -63.9 degrees (range, -204 degrees to -10.0 degrees) for the pre-PCI state, whereas it was 10.4 degrees (range, -71.1 degrees to 25.4 degrees) in the post-PCI state, i.e., more asynchronous in the pre-PCI state. SPA has been reported to influence the secretion of vasoactive molecules (e. g., nitric oxide, PGI(2), and endothelin-1), and asynchronous SPA (approximate to -180 degrees) is proposed to be proatherogenic. Our results suggest that differences in the pulsatile flow waveform may have an important influence on atherogenesis, although associated with only minor changes in the time-averaged wall shear stress and oscillatory shear index. SPA may be a useful indicator in predicting sites prone to atherosclerosis.